MANUSIA DAN HISTORISIT ASNYA MENURUT MARTIN HEIDEGGER - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Heidegger views "freedpm" and "transcendence" (retrospective consciousness) as the element that determines "the way of human existence" and also the human understanding of "history" radically. Philosophy of history is the main point of Heidegger's philosophy. It is showed by his most fundamental concept of "temporality". Heidegger so far develops the basic characteristic of relationship of "Being" (reality) and "time" (horizon) as a dialectical relationship. Because of his "poetic" nuance, Heidegger often makes someone confused for his call for "Being" as a "person", e.g., it as "the giver of blessing". Heidegger brings to the "true" understanding that all philosophical inquiries . startandendin theunderstandingofhumanbeing.